2021
DOI: 10.3390/membranes11010035
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Amino-Functional UiO-66/PIMs Mixed Matrix Membranes with [bmim][Tf2N] as Regulator for Enhanced Gas Separation

Abstract: Development of mixed matrix membranes (MMMs) with excellent permeance and selectivity applied for gas separation has been the focus of world attention. However, preparation of high-quality MMMs still remains a big challenge due to the lack of enough interfacial interaction. Herein, ionic liquid (IL)-modified UiO-66-NH2 filler was first incorporated into microporous organic polymer material (PIM-1) to prepare dense and defect-free mixed matrix membranes via a coating modification and priming technique. IL [bmim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 50 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…1c can be assigned to the symmetric and asymmetric extension of the –CH 2 – group in the [BMIM] (+) alkyl chain. 30–32 These results confirmed the successful loading of ILs into M1–M3. Compared with M0, the –COOH characteristic peak of M1–M3 membranes shifted from 1700 cm −1 to 1670 cm −1 (Fig.…”
Section: Resultssupporting
confidence: 60%
“…1c can be assigned to the symmetric and asymmetric extension of the –CH 2 – group in the [BMIM] (+) alkyl chain. 30–32 These results confirmed the successful loading of ILs into M1–M3. Compared with M0, the –COOH characteristic peak of M1–M3 membranes shifted from 1700 cm −1 to 1670 cm −1 (Fig.…”
Section: Resultssupporting
confidence: 60%
“…25 Interestingly, this approach has been followed to prepare a mix of both solid particles and ILs, which is now gaining special attention due to the possibility of boosting the gas separation performance of membranes by combining their properties. Lu et al 26 prepared PIM-1 mixed matrix membranes (MMMs) with an IL-modified UiO-66-NH 2 filler. They found that the IL improved not only the hydrophobicity of UiO-66-NH 2 , thus facilitating the dispersion of the particles into the polymer, but also the affinity between the MOF and polymer.…”
Section: Introductionmentioning
confidence: 99%
“…25 Interestingly, this approach has been followed to prepare a mix of both solid particles and ILs, which is now gaining special attention due to the possibility of boosting the gas separation performance of membranes by combining their properties. Lu et al 26 prepared PIM-1 mixed matrix membranes (MMMs) with a Instituto de Nanociencia y Materiales de Aragón (INMA), CSIC-Universidad de Zaragoza, Zaragoza 50018, Spain. E-mail: coronas@unizar.es b Chemical and Environmental Engineering Department, Universidad de Zaragoza, Zaragoza 50018, Spain † Electronic supplementary information (ESI) available.…”
Section: Introductionmentioning
confidence: 99%
“…This nature provides an opportunity for improving the mechanical and thermal stabilities of the hybrid membranes, as well as their ionic conductivity [23]. To sum up, incorporating MOFs in hybrid ion exchange membranes would acquire unique advantages over other nanostructure materials [24,25]. Incorporating acid-grafted inorganic fillers into the polymer matrix can increase the proton conductivity and interfacial compatibility of the composite membranes.…”
Section: Introductionmentioning
confidence: 99%